Predator ebook A crossbow novel. - Smith, Wilbur (2016)
Former operative Major Hector Cross must face off against a pair of lethal enemies and prevent an international catastrophe in this gripping contemporary adventure-thriller—perfect for fans of Clive Cussler, Ted Bell, and Vince Flynn—from the legendary worldwide bestselling author of Desert God and Golden Lion. One of the most formidable fighters in the world, ex-SAS warrior and former private security consultant Major Hector Cross has survived explosive tangles with depraved enemies—warlords, pirates, and arms dealers—from the Middle East to the heart of Africa. Now, Cross must take the law into his own hands once again to stop a vengeful old enemy who has resurfaced—and hunt down a deadly new nemesis in pursuit of global domination. Co-written with internationally bestselling author Tom Cain, this exciting tale, filled with knife-edge tension, cunning global intrigue, rip-roaring action, and breathtaking adventure, demonstrates the extraordinary vision and talent of a writer with a gift for consistently delivering nonstop entertainment.